Evaluation of muscle energy in isometric maintenance as an index of muscle fatigue in roller speed skating - Giulia Bongiorno; Helena Biancuzzi; Francesca Dal Mas; Luca Miceli (Frontiers Media S.A., 2023)
Roller speed skating is a discipline in which muscle fatigue plays an important role in athletes; in this work, we wanted to evaluate whether a methodological approach based on the energy required to maintain an isometric muscle contraction for one minute, indexed on the MVIC (maximum voluntary isometric contraction), i.e. % RMS/MVIC can give results similar to the frequency decay analysis/time in terms of usability for athlete training and injury prevention. Right and left gluteus maximus and vastus lateralis muscles (involved in the propulsive phase of skating ) were examined separately by surface electromyography in three competitive athletes in short-track speed skating on asphalt. The results showed an asymmetry between the right (less resistant) and left (more resistant) lower limb, in all three athletes, from the point of view of fatigue, in both investigated muscles. Furthermore, a trend in terms of fatigue resistance was found that was directly proportional to skill in both muscles studied. This can be of help in better planning the training of street speed skaters (which although similar to the discipline on ice is not completely superimposable) with the dual purpose of improving their performance and preventing injuries, often linked to the degree of right-left muscle asymmetry.